Management of anterior dental crossbite with removable appliances - Ayca Tuba Ulusoy; Ebru Hazar Bodrumlu (Wolters Kluwer Medknow Publications, 2013)
This case report describes the treatment of an 8-year-old girl with anterior dental crossbite using a series of removable appliances to bring the teeth into a normal position. Clinical presentation and intervention: A removable acrylic appliance with a bite plate incorporating a screw was used to correct the anterior dental crossbite and align the incisors. The subsequent eruption of the maxillary left lateral incisor on the palatinal side was treated with a second acrylic plate incorporating a labiolingual spring. After an 8-month period, the anterior crossbite involving multiple incisors was corrected.